1H‐1, 2, 3‐triazole‐tethered uracil‐ferrocene and uracil‐ferrocenylchalcone conjugates: Synthesis and antitubercular evaluation. (29th November 2016) - Singh, Amandeep; Biot, Christophe; Viljoen, Albertus; Dupont, Christian; Kremer, Laurent; Kumar, Kewal; Kumar, Vipan
Abstract : Copper‐catalyzed azide‐alkyne [3 + 2] cycloaddition has been utilized for preparing a series of 1 H ‐1, 2, 3‐triazoles with the purpose of probing structure–activity relationships among a uracil‐ferrocene‐triazole conjugate family. The antitubercular evaluation studies revealed an improvement in activity with the introduction of a ferrocene nucleus among N ‐alkylazido‐uracil precursors, with a preference for a bromo‐substituent along with moderate chain lengths of n  = 2–6. The reported protocol is a successful approach for integrating uracil‐ferrocene‐chalcone functionalities tethered via 1 H ‐1, 2, 3‐triazole rings with apparent physicochemical stability. Abstract : Synthesis and antitubercular evaluation of 1 H ‐1, 2, 3‐triazole‐tethered uracil‐ferrocene and uracil‐ferrocenylchalcone conjugates.